Hydrogen Sulfide Maintained the Good Appearance and Nutrition in Post-harvest Tomato Fruits by Antagonizing the Effect of Ethylene - Yao, Gai-Fang; Li, Chuang; Sun, Ke-Ke; Tang, Jun; Huang, Zhong-Qin; Yang, Feng; Huang, Guan-Gen; Hu, Lan-Ying; Jin, Peng; Hu, Kang-Di; Zhang, Hua (Frontiers in Plant Science, 2020)
Hydrogen sulﬁde (H2S) could act as a versatile signaling molecule in delaying fruit ripening and senescence. Ethylene (C2H4) also plays a key role in climacteric fruit ripening, but little attention has been given to its interaction with H2S in modulating fruit ripening and senescence. To study the role of H2S treatment on the fruit quality and nutrient metabolism, tomato fruits at white mature stage were treated with ethylene and ethylene plus H2S. By comparing to C2H4 treatment, we found that additional H2S significantly delayed the color change of tomato fruit, and maintained higher chlorophyll and lower flavonoids during storage. Moreover, H2S could inhibit the activity of protease, maintained higher levels of nutritional-related metabolites, such as anthocyanin, starch, soluble protein, ascorbic acid by comparing to C2H4 treatment. Gene expression analysis showed that additional H2S attenuated the expression of beta-amylase encoding gene BAM3, UDP-glycosyltransferase encoding genes, ethylene-responsive transcription factor ERF003 and DOF22. Furthermore, principal component analysis (PCA) suggested that starch, titratable acids and ascorbic acid were important factors for affecting the tomato storage quality, and the correlation analysis further showed that H2S affected pigments metabolism and the transformation of macromolecular to small molecular metabolites. These results showed that additional H2S could maintain the better appearance and nutritional quality than C2H4 treatment alone, and prolong the storage period of postharvest tomato fruits.